Performance evaluation of international trade fair exhibitors in Peru: The case of exhibitors in international trade fairs Peru moda and Peru gift of the year 2010 - Angles Sánchez, Enrique (2017)
International trade fairs are an international marketing instrument usually used by the exporting companies. Despite the benefits of international trade fairs, Peruvian exporting companies have a limited participation as exhibitors in them. There is no evidence to show how Peruvian exhibitors assessed their participation in international trade fairs. The main objective of the study is to analyze through which dimensions exhibiting companies evaluate their exhibition performance at international trade through sales results. Therefore, we decided to work with a model of trade fair performance of exhibiting companies including a dimension based on sales results. The study is quantitative and the research is correlational. The hypothetical deductive method was used and survey was determined as data collection instrument. As a result it appears that within the dimension of sales there is a strong positive and significant correlation between the level of sales to existing customers and the level of sales to new customers.